Mucolytic Therapy for Respiratory Diseases in Children - Yu.K. Bolbot (Zaslavsky O.Yu., 2015)
Pathogenetic mechanisms of mucociliary clearance disorders at respiratory pathology in children had been discussed. The analysis of drugs with mucolytic action, their effectiveness and safety had been carried out.